Impact of User Expertise, Technological Sophistication, and Management Participation on Accounting Information Systems Effectiveness - Pradana, I Gede Surya Bayu; Putra, I Nyoman Wijana Asmara (E-Jurnal Akuntansi; Vol 35 No 5 (2025)DO - 10.24843/EJA.2025.v35.i05.p11, 2025)
Effectiveness evaluates how successfully objectives are met concerning both time and quality, emphasizing the outcomes produced. This study investigates the influence of user expertise, technological sophistication, and management participation on the effectiveness of accounting information systems within BPRs in Gianyar Regency. A purposive sampling method was employed, selecting 24 BPRs and 120 respondents for the analysis. The results are supported by the Technology Acceptance Model (TAM). Through multiple linear regression analysis, the study finds that user expertise, technological sophistication, and management participation positively influence the effectiveness of accounting information systems. The research highlights the importance of enhancing these factors within BPRs to improve system effectiveness, usability, and overall benefits. Keywords: User Expertise, Technological Sophistication, Management Participation, Effectiveness of Accounting Information Systems, Technology Acceptance Model.